Integrated molecular characterization of chondrosarcoma reveals critical determinants of disease progression - Rémy Nicolle (Nature Portfolio, 2019)
Chondrosarcomas are heterogenous tumours of the bone cartilage and have highly variable prognoses. Here, the authors perform a multi-omics analysis, revealing molecular features that can stratify clinical outcomes.